Nidificación de Thamnophilus doliatus en Argentina - Di Giacomo, Alejandro G. (1998)
Five nests of the Barred Antshrike (Thamnophilus doliatus) were studied at the southern extreme of its distribution, in Formosa Province, Argentina. The laying interval was alternate days. The incubation period was 15 days and the nestling period 12-13 days. Nesting success was 33, 3 %. Brood parasitism of the Shiny Cowbird (Molothrus bonarienis) on nests of this antbird is reported for the first time. Clutch size seems to be about two eggs throughout the species ranges, but further information on this point is needed.